Implementasi Strategi Pemasaran Dengan Menggunakan Multimedia - Bowo, Ferdian Arie (Postgraduate of Jayabaya University, 2023)
In analyzing the data in multimedia, it is necessary to understand that there are differences in each media. For example, data contained in photos and audio that come from one media source, it is important to know the relationship between the two in a marketing strategy analysis. Descriptive research is the method used in this study using a qualitative approach. The findings of this study show that these multimedia developers not only practice management techniques, but need to consider marketing management strategies using multimedia as very important for the success of an increase in sales. The importance of good marketing management skills is emphasized by all consumers who will be interviewed. Whether it is proposal, team, budget, or design management, marketing management is a key ingredient for success. And it is an essential part of a manager's responsibilities in today's competitive multimedia marketplace.